(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The mechanisms of the increased vascular tone associated with vaso-occlusive crisis of sickle cell disease have not been clearly defined. The goal of the present study was to examine the role of vascular smooth muscle membrane Na+-K+-ATPase enzyme activity as well as nitric oxide synthase inhibition on the contractile responses induced by sickle erythrocyte constituents. 2 mm ring segments of rabbit carotid arterial ring preparations were placed in 20 ml organ baths containing physiological salt solution (PSS) bubbled with 95% O2, 5% CO2, at 37oC and pH 7.4 and isometric contractions recorded, under an initial load of 2g. Arterial rings were exposed to 50 µl of each erythrocyte constituent at an adjusted haematocrit of 0.6. The magnitude of K+-induced relaxation of 10-7 M phenylephrine (PE)-precontracted rings exposed for 30 minutes to K+-free PSS (which inhibits Na+-K+ pump) was estimated in the absence (control) or presence of RBC constituents (ghosts, erythrocytes or haemoglobin solution) from Hb SS subjects. Secondly, the influence of 20-minute exposure of the rings to SS GHOSTS on acetylcholine-induced, endothelium-dependent relaxation of 10-7 M PE phenylephrine-precontraction (in the absence or presence of L-NAME) was evaluated. Our results show that K+-induced relaxation was significantly and differentially attenuated by erythrocyte constituents (p<0.05) in the order: SS GHOST > SS HBS > SS RBC. NO synthase inhibition with L-NAME further potentiated the enhanced PE contractions induced by SS GHOSTS and caused a greater attenuation of Ach-induced relaxation (compared with SS GHOSTS alone). The results suggest that SS erythrocyte GHOSTS induce enhancement of vascular smooth muscle tone via impairment of vascular Na+-K+ ATPase enzyme activity as well as attenuate endothelium-dependent relaxation. These functional changes in vascular smooth muscle and endothelial function may contribute to the pathophysiology of vaso-occlusive crisis of sickle cell disease